Relationship Level of Knowledge About Covid-19 With Physical Distancing Program Compliance in Adolescents - Risnah Risnah; Muhammad Irwan (Fakultas Kedokteran, 2022)
Coronavirus 2019 (Covid-19) is a disease that has become a worldwide pandemic. Covid-19 infection can cause mild, moderate, or severe symptoms. Covid-19 can be transmitted from humans through close contact and droplets, not through the air. The World Health Organization recommends implementing 3M, namely washing hands, wearing masks, and physical distancing. To find out the relationship between the level of knowledge about the Covid-19 physical distancing program in adolescents. This research is a quantitative study with a cross sectional design, with a sampling technique using a total sampling technique, data obtained from a google form filled out by respondents. The results showed that 46% of respondents had good knowledge, 52.1% had a fairly good level of knowledge, and 1.9% of respondents had a poor level of knowledge about Covid-19. The respondents who implemented physical distancing were as many as 86% of respondents and those who did not apply as many as 14%. From the cross tabulation calculation between the level of knowledge about Covid-19 and compliance with the physical distancing program using SPSS with the chi-square test, the p-value is 0.000 with a significant level of 0.05. There is a significant relationship between knowledge about Covid-19 and compliance with physical distancing programs.